CHARACTERIZING THE BINDING SITE OF GPVI INHIBITORS FOR THE DEVELOPMENT OF NOVEL ANTI-PLATELET AGENTS - Damaskinaki, Foteini-Nafsika (2023)
Ischemic cardiovascular and cerebrovascular diseases are two of the major disorders responsible for deaths and morbidity globally. Blood platelets play an important role in prevention of excessive bleeding and wound healing and their dysregulation can have a great impact in the former pathologies. Current antiplatelet therapies have an intrinsic bleeding risk which can even result to life-threatening bleeding. The platelet collagen receptor GPVI has emerged as a promising target for long-term prevention of both arterial thrombosis and inflammation-driven thrombosis with a lower bleeding risk and a minimal effect on haemostasis. Due to the decreased bioavailability of current anti-GPVI biological agents, formulating oral medication against GPVI. However, the nature of GPVI extracellular domain structure and multiple sites of interaction within GPVI are limiting the development of small molecule inhibitors. The aim of this thesis is to develop and characterise selective small molecule inhibitors and nanobody GPVI ligands in order to map the binding sites within GPVI to aid future design of inhibitors. The methodological approach included the use of a structural-based virtual screening, with subsequent testing, and a combination of mutation studies with protein crystallography of GPVI in complex with potent nanobody (Nb) ligands. Although compound 22 showed promising results on collagen-induced aggregation, fluorescence-based assays ruled out this molecule as a selective GPVI inhibitor. The crystal structure of a new potent anti-GPVI nanobody, Nb35, in complex with the extracellular domain of GPVI was resolved, revealing an overlapping binding site and similar binding coordinates with that of Nb2. Mutation studies revealed GPVI residue R46 as a residue important for the inhibitory function of Nb2, Nb21 and Nb35 on collagen signalling while R60 is important for the interaction with Nb21 but not Nb2 and Nb35. These findings are highly applicable in the future design of screening strategies for potent small molecule GPVI inhibitors.